Blood Glucose Testing on Blood Donors and Geriatrics in the Area of Mosque Al-Akbar Surabaya - museyaroh, museyaroh; Juliana Christyaningsih; Retno Sasongkowati; Suliati; Anita Dwi Anggraini; Deddy Adam; Toni Watoyani; Makruf, Anang; Safrudin, Samsul; Isnaini, Dian; M. Zakarahman; Sugihani; Kristiningsih, Elly; Puspitasari, Erlita; Ersanto, Novi; Novita, Devy; Kuswanto, Muhammad; Trisnania, Iid Dani; Rusmania, Liya; Haqqi, Faishol; Saktiyani, Fisari; Briansky, Sabira Alvayogi (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
The Indonesian Red Cross (IRC) is a humanitarian organization that plays an important role in providing assistance to the community, particularly in the fields of health, disaster response, and blood donation services. The volunteer team from Health Polytechnic, Ministry of Health, Surabaya, in collaboration with members of the Indonesian Association of Medical Laboratory Technologists Surabaya city and IRC Surabaya city, conducted free blood glucose level tests for prospective donors and the elderly (geriatric) in Al-Akbar Mosque Surabaya. This examination aims to detect potential health issues early, especially diabetes, which often poses challenges for blood donors and the elderly. Blood donors tend to neglect their health conditions due to the donation routine, so this examination ensures that they remain in optimal condition. Meanwhile, the elderly have a high risk of diabetes, which can affect their quality of life. The strategic location at Al-Akbar Mosque Surabaya facilitates access for the community who are far from the IRC Surabaya city office. The success of this activity is supported by various factors, including the involvement of professional health organizations such as the branch Surabaya City of Indonesian Association of Medical Laboratory Technologists, the support of health infrastructure from IRC Surabaya city, and the active participation of the community and volunteers. The respondents of the community service activity numbered 88 people, conducted on March 15 and 17, 2025, consisting of 59% men and 41% women, with an age range of 20-80 years and the majority of respondents aged 41-60 years (56.8%). From the examination results, it was found that 21% of male respondents and 13.9% of female respondents suffer from diabetes mellitus (DM), thus requiring medical follow-up and lifestyle changes. This activity is expected to raise public awareness about the importance of early diabetes detection and encourage a sustainable healthy lifestyle to prevent serious complications in the future